Endoscopic stapes surgery: How I do it? - Shrestha, B. L. (Kathmandu University Medical Journal, 2021)
The use of endoscope in the field of ear surgery has done the revolutionary changes. The optical advantage of endoscope helps the otologist to perform the stapes surgery very conveniently. The main advantage of the endoscope in stapes surgery over the microscope is; the better preservation rates of the chorda tympani nerve (CTN), minimal curetting of the outer attic wall, hence minimizing the iatrogenic injury to the CTN. Apart from that, the audiometric results following the endoscopic stapes surgery is comparable with the microscopic surgery. We had performed the stapes surgery with the rigid nasal endoscopes (Karl Storz) of 4-mm diameter and 18-cm length. Our preliminary results showed that transcanal endoscopic stapedotomy is a reliable and safe technique for the surgical management of otosclerosis.